SUSTAINABILITY AND CHALLENGES OF MARITIME DEFENSE COOPERATION IN THE ERA OF AUKUS: AN INDO-PACIFIC PERSPECTIVE - Syafi, Alif Naufal; Seniwati, Seniwati (Triwikrama: Jurnal Ilmu Sosial, 2024)
This article examines the sustainability and challenges of maritime defense cooperation in the AUKUS era from an Indo-Pacific perspective. The AUKUS trilateral alliance, comprising Australia, the United Kingdom and the United States, was formed with the aim of enhancing maritime security in the Indo-Pacific region to counter China's growing military influence. This article analyses the geopolitical, economic, and technological factors affecting the alliance's sustainability, including potential tensions in the South China Sea and mixed reactions from ASEAN countries. In addition, AUKUS's internal challenges related to technology transfer, compliance with international law, and infrastructure and human resource training needs are reviewed. The article concludes that the success of AUKUS largely depends on member state’s ability to build trust and transparency to maintain maritime stability and security in the Indo-Pacific region, while adjusting to changing geopolitical dynamics.